2011
DOI: 10.1039/c0sc00466a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and utility of fluorogenic acetoxymethyl ethers

Abstract: Phenolic fluorophores such as fluorescein, Tokyo Green, resorufin, and their derivatives are workhorses of biological science. Acylating the phenolic hydroxyl group(s) in these fluorophores masks their fluorescence. The ensuing ester is a substrate for cellular esterases, which can restore fluorescence. These esters are, however, notoriously unstable to hydrolysis, severely compromising their utility. The acetoxymethyl (AM) group is an esterase-sensitive motif that can mask polar functionalities in small molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
116
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(126 citation statements)
references
References 55 publications
4
116
0
2
Order By: Relevance
“…We determined the catalytic constants of PLE unmasking of fluorescein-CM 2 (6) and compared them to the unmasking of fluorescein-AM 2 (1) as shown in Fig. S3 B and C. Masked fluorophore 1 was cleaved by PLE with apparent catalytic constants k cat ∕K M ¼ 5.8 AE 0.9 × 10 5 M −1 s −1 (mean AE SE) and K M ¼ 2.7 AE 0.4 μM, in agreement with previously published values (17). The CM derivative 6 was cleaved more slowly, exhibiting apparent catalytic constants of…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…We determined the catalytic constants of PLE unmasking of fluorescein-CM 2 (6) and compared them to the unmasking of fluorescein-AM 2 (1) as shown in Fig. S3 B and C. Masked fluorophore 1 was cleaved by PLE with apparent catalytic constants k cat ∕K M ¼ 5.8 AE 0.9 × 10 5 M −1 s −1 (mean AE SE) and K M ¼ 2.7 AE 0.4 μM, in agreement with previously published values (17). The CM derivative 6 was cleaved more slowly, exhibiting apparent catalytic constants of…”
Section: Resultssupporting
confidence: 76%
“…We limited this series to contain small, commercially available, achiral esters with different α-carbon substitution patterns encompassing a range of steric and stereoelectronic properties. Compounds 1-6 show low background fluorescence in the masked form, and hydrolysis of the ester bonds ultimately releases the bright green fluorophore, fluorescein (17). In addition to high contrast, chemical stability is important for accurate determination of cellular esterase activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First it was necessary to mask the acidic groups on resorufin as an acetoxymethyl (AM) ester and ether to give resorufin-AM 2 . This probe readily crossed cell membranes; endogenous esterases then cleave the masking groups to regenerate resorufin (27). We observed that resorufin-AM 2 has two regioisomers, cis and trans (SI Appendix, Fig.…”
Section: Structure-based Mutagenesis and Screening For Resorufin Ligasementioning
confidence: 97%